PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, SUPERVISI DAN KEPUASAN KERJA GURU TERHADAP KINERJA GURU MIPA DI YAYASAN PENDIDIKAN ADVENT TIMIKA. - Tiogas, Donald M. F.; Walukow, Auldry F. (Magister Pendidikan IPA, UNCEN, 2014)
In this study, a research has been conducted from July until December 2013 in order to determine The Relationship Among The Principals Leadership, Supervision and the Teachers Work Satisfaction Towards The Work Performance of The Science Teachers in Timika Adventist Academy. Furthermore, descriptive analysis was used during the process of research. The population of this study is the science teachers of Timika Adventist Academy with 23 teachers as sample. The instrument being used in collecting the data is quetionnaire and the data analysis uses SPSS version 16.0 application. The result of the reseach show that the principal leadership has a significant influence toward the science teachersâ work performance about 73,10%. While the supervision done by principal toward the same teachers contributes 55,10%. The rest about 72,42% is the contribution of the teachers work satisfaction. In conclusion all togather, the principal leadership, supervision, and the teachers work satisfaction have significant influence toward the Timika Adventist Academy science teachersâ work performance about 84,10%. Those factors respectively has role in achieving an optimal teachers work performance. Keywords: Principals leadership, supervision, work satisfaction.